A Comparison Study between Parasitological and Molecular Methods for Diagnosis of Acute and Chronic Anthroponotic Cutaneous Leishmaniasis - Susan Darudi; Mehdi Mohebali; Homa Hajjaran; Abdolmajiid Fata; Elham Kazemi-Rad; Reza Raoofian (Pasteur Institute of Iran, 2015)
Introduction: Anthroponotic cutaneous leishmaniasis (ACL) is still a major public health problem in the northeast and central parts of Iran. This study was designed to compare microscopy and cultivation methods with PCR amplification of kinetoplast DNA and ITS1 followed by RFLP analysis for diagnosis of acute and chronic ACL. Methods: In this study, 66 patients with ACL including 24 acute and 42 chronic forms were analyzed. Chronic forms (n=42) were divided into lupoid (n=18) and non-lupoid forms (n=24). The exudates from patient's lesions were examined by parasitological and molecular methods. Results: Out of 24 acute ACL cases, 24 (100%), 20 (83.3%), 24 (100%) and 23 (95.8%) were positive with direct examination, cultivation, kDNA-PCR, and ITS1-PCR-RFLP, respectively; while among 42 chronic forms, 29 (69%), 12 (28.5%), 27 (64.2%) and 16 (38%) were positive with the above mentioned methods. The most positivity rate was obtained with the direct examination for all clinical forms of ACL. In comparison with the direct examination as a gold standard, the kDNA-PCR showed the highest sensitivity of 100% and 64.2% in the diagnosis of acute and chronic forms, followed by the ITS1-PCR with lower sensitivity (95.8% and 38%) and then cultivation (83.3% and 28.5%). Also, all of the Leishmania isolates were identified as Leishmania tropica based on clinical symptoms and molecular methods. Conclusion: Our results recommend application of direct examination for the diagnosis of both acute and chronic forms of ACL. Moreover, the molecular method using kDNA-PCR was proposed for the diagnosis of ACL; while ITS1-PCR-RFLP can be utilized as a useful technique for the Leishmania species identification of CL.